Help on this question pleaseeeeeeee
![Help on this question pleaseeeeeeee class=](https://us-static.z-dn.net/files/d2f/c5129501eab84fc5905d97dca31a4c29.png)
Step-by-step explanation:
F-27=19
F= 19+27
F=46
I hope it is helpful have a nice day
Answer:
answer is 46
Step-by-step explanation:
Solution for f-27=19 equation:
Simplifying
f + -27 = 19
Reorder the terms:
-27 + f = 19
Solving
-27 + f = 19
Solving for variable 'f'.
Move all terms containing f to the left, all other terms to the right.
Add '27' to each side of the equation.
-27 + 27 + f = 19 + 27
Combine like terms: -27 + 27 = 0
0 + f = 19 + 27
f = 19 + 27
Combine like terms: 19 + 27 = 46
f = 46
Simplifying
f = 46